MnFtz-f1 Is Required for Molting and Ovulation of the Oriental River Prawn Macrobrachium nipponense - Yuan, Huwei; Zhang, Wenyi; Fu, Yin; Jiang, Sufei; Xiong, Yiwei; Zhai, Shuhua; Gong, Yongsheng; Qiao, Hui; Fu, Hongtuo; Wu, Yan (Frontiers in Endocrinology, 2021)
Molting and ovulation are the basis for the growth and reproduction of Macrobrachium nipponense, but the molecular mechanisms of molting and ovulation of M. nipponense are poorly understood. The aim of the work was to use MnFtz-f1 as the starting point to study the molting and ovulation phenomena of M. nipponense at the molecular level. The full-length MnFtz-f1 cDNA sequence was 2198 base pairs (bp) long with an open reading frame of 1899 bp encoding 632 amino acids. Quantitative real-time PCR analysis showed that MnFtz-f1 was highly expressed in the ovary, cleavage stage and the fifth day after hatching. Injecting 20-Hydroxyecdysone in vivo proved that 20E could effectively inhibit the expression of MnFtz-f1 gene, and the silence of MnFtz-f1 gene could reduce the 20E content in the ovary. In situ hybridization analysis showed the location of MnFtz-f1 in the ovary. RNA interference silencing of MnFtz-f1 caused the expression of Vg, Spook and Phantom genes to be significantly inhibited, proving that MnFtz-f1 had a mutual regulatory relationship with Vg, Spook and Phantom. After interference, the molting frequency and ovulation number of M. nipponense decreased significantly, which proved that MnFtz-f1 played a pivotal role in the process of molting and ovulation.